Attendance in a Neonatal Follow-Up Program before and in the Time of COVID-19 Pandemic: A Mixed Prospective-Retrospective Observational Study - Evdoxia Nantsi; Ilias Chatziioannidis; Abraham Pouliakis; Georgios Mitsiakos; Elias Kondilis (MDPI AG, 2024)
Background: Attendance to neonatal follow-up programs presents a significant factor associated with positive long-term outcomes of high-risk infants. Strategies to maximize participation benefit not only future interventions' effectiveness but also healthcare systems and society. While a number of studies have focused on attrition or loss to follow-up, no studies have focused on the contributive risk factors to abstaining from neonatal follow-up programs specifically during the COVID-19 pandemic. This study aims to reveal the main factors linked to non-compliance in a neonatal follow-up program of a tertiary hospital. Methods: In this ambidirectional observational study, data from 1137 high-risk neonates who participated in a hospital follow-up program were collected (573 before and 564 after the COVID-19 pandemic). The study sample was grouped to three groups: G1 (N = 831), who maintained participation in the program; G2 (N = 196), who discontinued; and G3 (N = 110), who never visited the outpatient clinics. Data were obtained from the hospital's Systems Applications and Products (SAP) Software and a structured questionnaire, answered by parents of newborns either discontinuing (G2) or not attending (G3) the follow-up program through a telephone contact. Results: The most frequently reported reason for discontinuance before the pandemic onset was the parents' perception of no necessity to maintain participation (44.12%). During the COVID-19 pandemic, provider-related barriers to maintaining hospital access, inability to provide high-quality services (37.14%), and feelings of fear and insecurity (18.5%) emerged as factors for non-attendance. Citizenship and morbidity (respiratory distress syndrome, sepsis, necrotic enterocolitis, jaundice) acted as incentives to join the follow-up program during both study periods. Multiple regression analysis showed that multiple-gestation infants had higher odds of maintaining participation during the COVID-19 period (OR, 4.04; CI, 1.09-14.9). Conclusions: Understanding the potential impact of COVID-19 and the transformative changes in neonatal follow-up clinics is crucial for applying compliance strategies. Removing barriers to maintain family participation can lead to increased attendance rates.